Effective role of the ‘loading’ dose of magnesium sulfate in the treatment of eclampsia - Khatun, Halima; Islam, M. Saiful; Islam, Tarikul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Eclampsia is defined as the occurrence of one or more convulsions in association with the syndrome of preeclampsia. In Bangladesh, eclampsia is the 3rd major cause of maternal death. Magnesium sulfate is now the drug of choice for women with eclampsia for controlling convulsion with strong evidence that it is better than diazepam, phenytoin or lytic cocktail. Aim of the study was to find out the effective role of loading dose of magnesium sulfate in the treatment of the convulsion in eclampsia. Methods: Prospective comparative study. In the Department of Obstetrics and Gynaecology, Rajshahi Medical College Hospital (RMCH)" from January 2008 to December 2008. A total of 100 eclamptic patients who are eligible for magnesium sulfate therapy were purposively assigned to receive either only loading "dose or traditional dose for control of convulsion. Data was organized and the results were presented in tables, figures, diagram etc. by using SPSS-10 and MS-Excel 2016. Results: The mean (±SD) convulsion (fit) and delivery interval was 7.95±1.33. Regained consciousness was predominant 28(56.0%) patients after initiation of treatment. Maternal death was found 1 (2.00%). The cause of maternal mortality was due to renal failure. The mean (±SD) respiratory rate was 20.2±4.19min. Normal urine was found 43(86.0%). Normal knee jerks were found 45 (90.0%). No toxicity developed in any group assessed by the parameters like respiratory rate, urine volume and knee jerks. Conclusions: For the above reasons eclampsia can be treated effectively by only loading dose of Mgs04 in primary as well as tertiary level hospital which will significantly reduce the maternal morbidity and mortality.